A review of post-whaling abundance, trends, changes in distribution and migration patterns, and supplementary feeding of Southern Hemisphere humpback whales - Seyboth, Elisa; Meynecke, Jan-Olaf; de Bie, Jasper; Roychoudhury, Alakendra; Findlay, Ken (Frontiers in Marine Science, 2023)
Southern Hemisphere humpback whales (Megaptera novaeangliae) were heavily targeted during modern commercial whaling operations, with some 216,000 individuals killed between 1903 and 1973. That impacted the abundance of all the seven breeding stocks of the species. Most of these stocks have been recovering from whaling pressure although the understanding of the current growth rates of some stocks, and how the rates compare across stocks are lacking. Updated information is fundamental for understanding the species’ current status, and to support the review of management plans promoting its protection and recovery, especially considering current changes in ocean environments due to climate change. This work offers a comprehensive overview of the current knowledge on Southern Hemisphere humpback whales breeding stocks’ status. The aim is to provide information on their post-whaling growth trends and changes in distribution and migration patterns. Within that, records of supplementary feeding records (i.e. feeding beyond their formally described feeding grounds) are described. We have also identified knowledge gaps and note that the establishment of research collaborations, as well as standard methodologies for data collection can be important steps for the acquisition of better comparable data sets for the analysis of the current status of humpback whales and to fill such gaps. The compiled information provided can be used as part of an In-Depth Assessment of the species by the International Whaling Commission.